The influence of price and facilities on guests' decision to stay at the Grand Arkenso Park View Hotel, Semarang - Amini, A'lamuna Yustika; Aswan, Mukhamad Kholil (Jurnal Mantik, 2024)
This research was conducted to determine the influence of price and facilities on guests' overnight decisions, where the object of this research was the Grand Arkenso Parkview Hotel Semarang. This research uses a quantitative approach with a sample size of 100 respondents. with data retrieval analysis techniques accidental sampling. The analytical data used includes instrument tests consisting of validity and reliability tests, then hypothesis tests consisting of partial tests or t tests, simultaneous tests or F tests coefficient of determinationor R2 test, and multiple linear test. From the research results it was found that there wereThe influence of price on guests' decision to stay.The influence of facilities on guests' decision to stay, and there is pThe influence of price and facilities on guests' decision to stay at the Arkenso Park View Hotel, Semarang